Estimating the value of adventure tourism resources using travel cost method in Kampar, Perak, Malaysia - Mohamed, Zulkifli (2018)
The adventure tourism industry in Kampar is highly dependent on its non-market goods, which in this case, is the natural resources that provide outdoor adventure experiences. Being endowed with abundant natural resources such as caves, rivers, waterfalls, and forests, Kampar has undoubtedly become one of the best destinations for adventure tourism in Malaysia. From 2016 to 2017, the Perak state government had spent a total of RM 25.5 million in the upgrading, maintenance and promotion of tourism products in Perak. On top of that, the local government had also allocated RM 53.52 million in its plan of developing Kampar as an important hub for eco-adventure tourism in Perak (Rancangan Tempatan 2030). Kampar had also been chosen as one of the 60 pilot ecotourism clusters under the National Ecotourism Plan (2016-2025) that focused on adventure tourism activities. Since the government and the stakeholders had invested heavily in developing, maintaining and promoting Kampar as an adventure destination, therefore a study must be conducted as a means of estimating the economic value of adventure tourism resources and for the justification of the money and efforts spent by all related parties. Hence for the purpose of this research, the Individual Travel Cost Model (ITCM) had been utilised to meet the above objective. The study was conducted via face-to-face interviews with domestic visitors who had participated in at least one of the adventure tourism activities that are available in Kampar. The on-site data from 305 adventure tourists were collected and analysed by using linear regression. Based on the results, it can be concluded that the adventure travellers to Kampar not only consisted of the middle class and those with a high level education, they were also predominantly Malay and Chinese and within the 21-40 age group who mainly came from Perak, Selangor and Kuala Lumpur. The study revealed that the number of visits to Kampar was seen to be positively and significantly influenced by several variables such as individual travel cost, tour cost, and ethnicities. The findings revealed that, the consumer surplus value per trip per person to Kampar had been RM 452.48. Therefore, the economic value of the adventure tourism resource in Kampar for the year 2016 was estimated to be RM 20,064,320.64.